Daily field checking list by Walter Rosene, June 15, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated June 15, 1932. This checklist was used by Walter Rosene to record birds sighted around Long Pond with Philip DuMont and Walter Jr. between 7:30 and 6:00. Plustek--flatbed